Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine the correct truth values for the expression [tex]\(\sim( p \rightarrow q ) \rightarrow( p \wedge \sim q)\)[/tex], we need to create a truth table and evaluate each combination of [tex]\(p\)[/tex] and [tex]\(q\)[/tex].
Let's examine each row step by step:
1. For [tex]\(p = T\)[/tex] and [tex]\(q = T\)[/tex]:
- [tex]\(p \rightarrow q\)[/tex] is [tex]\(T \rightarrow T\)[/tex], which is [tex]\(T\)[/tex].
- [tex]\(\sim (p \rightarrow q)\)[/tex] is [tex]\(\sim T\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(p \wedge \sim q\)[/tex] is [tex]\(T \wedge \sim T\)[/tex], which is [tex]\(T \wedge F\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(\sim (p \rightarrow q) \rightarrow (p \wedge \sim q)\)[/tex] is [tex]\(F \rightarrow F\)[/tex], which is [tex]\(T\)[/tex].
2. For [tex]\(p = T\)[/tex] and [tex]\(q = F\)[/tex]:
- [tex]\(p \rightarrow q\)[/tex] is [tex]\(T \rightarrow F\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(\sim (p \rightarrow q)\)[/tex] is [tex]\(\sim F\)[/tex], which is [tex]\(T\)[/tex].
- [tex]\(p \wedge \sim q\)[/tex] is [tex]\(T \wedge \sim F\)[/tex], which is [tex]\(T \wedge T\)[/tex], which is [tex]\(T\)[/tex].
- [tex]\(\sim (p \rightarrow q) \rightarrow (p \wedge \sim q)\)[/tex] is [tex]\(T \rightarrow T\)[/tex], which is [tex]\(T\)[/tex].
3. For [tex]\(p = F\)[/tex] and [tex]\(q = T\)[/tex]:
- [tex]\(p \rightarrow q\)[/tex] is [tex]\(F \rightarrow T\)[/tex], which is [tex]\(T\)[/tex].
- [tex]\(\sim (p \rightarrow q)\)[/tex] is [tex]\(\sim T\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(p \wedge \sim q\)[/tex] is [tex]\(F \wedge \sim T\)[/tex], which is [tex]\(F \wedge F\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(\sim (p \rightarrow q) \rightarrow (p \wedge \sim q)\)[/tex] is [tex]\(F \rightarrow F\)[/tex], which is [tex]\(T\)[/tex].
4. For [tex]\(p = F\)[/tex] and [tex]\(q = F\)[/tex]:
- [tex]\(p \rightarrow q\)[/tex] is [tex]\(F \rightarrow F\)[/tex], which is [tex]\(T\)[/tex].
- [tex]\(\sim (p \rightarrow q)\)[/tex] is [tex]\(\sim T\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(p \wedge \sim q\)[/tex] is [tex]\(F \wedge \sim F\)[/tex], which is [tex]\(F \wedge T\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(\sim (p \rightarrow q) \rightarrow (p \wedge \sim q)\)[/tex] is [tex]\(F \rightarrow F\)[/tex], which is [tex]\(T\)[/tex].
Given these evaluations, the correct statement for the truth table should be:
\begin{tabular}{ccc}
[tex]$p$[/tex] & [tex]$q$[/tex] & [tex]$\sim( p \rightarrow q ) \rightarrow( p \wedge \sim q)$[/tex] \\
\hline
[tex]$T$[/tex] & [tex]$T$[/tex] & [tex]$F$[/tex] \\
[tex]$T$[/tex] & [tex]$F$[/tex] & [tex]$T$[/tex] \\
[tex]$F$[/tex] & [tex]$T$[/tex] & [tex]$F$[/tex] \\
[tex]$F$[/tex] & [tex]$F$[/tex] & [tex]$F$[/tex] \\
\end{tabular}
Thus, the answer is:
[tex]\[(T, T, F), (T, F, T), (F, T, F), (F, F, F)\][/tex]
Let's examine each row step by step:
1. For [tex]\(p = T\)[/tex] and [tex]\(q = T\)[/tex]:
- [tex]\(p \rightarrow q\)[/tex] is [tex]\(T \rightarrow T\)[/tex], which is [tex]\(T\)[/tex].
- [tex]\(\sim (p \rightarrow q)\)[/tex] is [tex]\(\sim T\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(p \wedge \sim q\)[/tex] is [tex]\(T \wedge \sim T\)[/tex], which is [tex]\(T \wedge F\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(\sim (p \rightarrow q) \rightarrow (p \wedge \sim q)\)[/tex] is [tex]\(F \rightarrow F\)[/tex], which is [tex]\(T\)[/tex].
2. For [tex]\(p = T\)[/tex] and [tex]\(q = F\)[/tex]:
- [tex]\(p \rightarrow q\)[/tex] is [tex]\(T \rightarrow F\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(\sim (p \rightarrow q)\)[/tex] is [tex]\(\sim F\)[/tex], which is [tex]\(T\)[/tex].
- [tex]\(p \wedge \sim q\)[/tex] is [tex]\(T \wedge \sim F\)[/tex], which is [tex]\(T \wedge T\)[/tex], which is [tex]\(T\)[/tex].
- [tex]\(\sim (p \rightarrow q) \rightarrow (p \wedge \sim q)\)[/tex] is [tex]\(T \rightarrow T\)[/tex], which is [tex]\(T\)[/tex].
3. For [tex]\(p = F\)[/tex] and [tex]\(q = T\)[/tex]:
- [tex]\(p \rightarrow q\)[/tex] is [tex]\(F \rightarrow T\)[/tex], which is [tex]\(T\)[/tex].
- [tex]\(\sim (p \rightarrow q)\)[/tex] is [tex]\(\sim T\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(p \wedge \sim q\)[/tex] is [tex]\(F \wedge \sim T\)[/tex], which is [tex]\(F \wedge F\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(\sim (p \rightarrow q) \rightarrow (p \wedge \sim q)\)[/tex] is [tex]\(F \rightarrow F\)[/tex], which is [tex]\(T\)[/tex].
4. For [tex]\(p = F\)[/tex] and [tex]\(q = F\)[/tex]:
- [tex]\(p \rightarrow q\)[/tex] is [tex]\(F \rightarrow F\)[/tex], which is [tex]\(T\)[/tex].
- [tex]\(\sim (p \rightarrow q)\)[/tex] is [tex]\(\sim T\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(p \wedge \sim q\)[/tex] is [tex]\(F \wedge \sim F\)[/tex], which is [tex]\(F \wedge T\)[/tex], which is [tex]\(F\)[/tex].
- [tex]\(\sim (p \rightarrow q) \rightarrow (p \wedge \sim q)\)[/tex] is [tex]\(F \rightarrow F\)[/tex], which is [tex]\(T\)[/tex].
Given these evaluations, the correct statement for the truth table should be:
\begin{tabular}{ccc}
[tex]$p$[/tex] & [tex]$q$[/tex] & [tex]$\sim( p \rightarrow q ) \rightarrow( p \wedge \sim q)$[/tex] \\
\hline
[tex]$T$[/tex] & [tex]$T$[/tex] & [tex]$F$[/tex] \\
[tex]$T$[/tex] & [tex]$F$[/tex] & [tex]$T$[/tex] \\
[tex]$F$[/tex] & [tex]$T$[/tex] & [tex]$F$[/tex] \\
[tex]$F$[/tex] & [tex]$F$[/tex] & [tex]$F$[/tex] \\
\end{tabular}
Thus, the answer is:
[tex]\[(T, T, F), (T, F, T), (F, T, F), (F, F, F)\][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.